Assessing The Ethical Behavior Of Accounting Accounts Through The Application Of The Tri Kaya Parisudha Philosophy On Equity Sensitivity and Ethical Sensitivity - DEWI, MERTYANI SARI; SARI DEWI, KOMANG TRISNA; FERAYANI, MADE DWI (International Journal of Social Science and Business, 2021)
Every person or worker in the world of work from various professions basically must be able to always prioritize ethical attitudes in carrying out their duties and obligations at work. The success of an information system cannot be separated from human behavior. The government must pay attention to the ability of its employees because they are required to have accountability that is able to develop a good and well-established reporting system. In order to realize effective financial administration, the role of PPK OPD is very vital, in other words, its capabilities and skills in preparing OPD Financial Report documents. The government must pay attention to the ability of its employees because they are required to have accountability that is able to develop a good and well-established reporting system. The phenomenon that can be observed in the development of the public sector today is the increasing demand for the implementation of public accountability by public sector organizations such as: central and local governments, government work units, departments and state institutions. Bangli Regency area which gets different opinions from BPK RI every year. The method used in this research is the Component based SEM, Partial Least Square (PLS) analysis method. To obtain data, a questionnaire technique was used as a means of collecting data. Questionnaires will be distributed to 25 OPD Bangli Regency.The test results show empirical evidence that equity sensitivity has a significant positive effect on the ethical behavior of accounting actors. second, ethical sensitivity has a significant positive effect on the ethical behavior of accounting actors. third, the philosophy of tri Kaya parisudha strengthens the influence of ethical sensitivity on the ethical behavior of accounting actors. Fourth, the Tri Kaya Parisudha philosophy strengthens the influence of ethical sensitivity on the ethical behavior of accounting actors.